Wind dispersed tree species have greater maximum height - Slik, Ferry; Pinho, Bruno X.; Griffith, Daniel M.; Webb, Edward; Raghubanshi, Akhilesh Singh; Quaresma, Adriano C.; Cuni Sanchez, Aida; Sultana, Aisha; Souza, Alexandre F.; Ensslin, Andreas; Hemp, Andreas; Lowe, Andrew; et al. (John Wiley and Sons, 2024)
Aim: We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location: Americas, Africa and the Asia-Pacific. Time period: 1970–2020. Major taxa studied: Gymnosperms and Angiosperms. Methods: We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia-Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind-dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind-dispersed in dry and wet forests within each biogeographic region. Results: Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non-emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion: Wind dispersal is more prevalent in tall, emergent tree species than in non-emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco-evolutionary drivers of tree size.